Diseñar una matriz para la selección de un método óptimo para la limpieza de arenas en pozos productores del campo la Cira Infantas (2020)
The present project consists of describing the generalities and geology of the Valle Medio de Magdalena basin by searching for information from Pappers, scientific articles, and books on Colombian geology, as well as the causes of sand production such as faults produced at scale grain, degree of compaction, fluid flow, geological factors, among others, as well as the effects caused by a high production of sand, which can lead to damage to pipes, surface equipment, accumulation of sand, loss of production, were described, even a catastrophic failure in the well. Then it was investigated what are the techniques used today for sand cleaning by western Colombia.